دراسة اتجاهات المستهلكين في محافظة اللاذقية لشراء المنتجات الوطنية - منصور يمن (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى التعرف على اتجاهات المستهلكين السوريين لشراء المنتجات الوطنية. وقد أشارت نتائج البحث إلى وجود اتجاهات سلبية لدى المستهلكين لشراء المنتجات الوطنية، وانحفاض تأثير عناصر المزيج الترويجي والجماعات المرجعية على اتجاهات المستهلكين لشراء المنتجات الوطنية. وأشارت توصيات البحث إلى ضرورة القيام بتغيير اتجاهات المستهلكين من اتجاهات سلبية قوية لشراء المنتجات الوطنية إلى اتجاهات إيجابية قوية لشراء المنتجات الوطنية، وضرورة القيام بحملات توعية في وسائل الإعلام لإقناع المستهلكين بأهمية شراء المنتجات الوطنية، وضرورة قيام الجماعات المرجعية وجمعية حماية المستهلك في تحفيز المستهلكين لشراء المنتجات الوطنية. The objective of this research is to highlight the Syrian consumer attitudes towards purchasing nationally manufactured products. The results of this research have indicted negative attitudes by consumers towards buying national products, and a decrease in the effect of promotion elements and consumer protection association on consumer attitudes towards purchasing national products. The recommendations of this research have stressed the need to start changing consumer attitudes from strong negative attitudes to strong positive attitudes towards purchasing national products, and the necessity of running awareness campaigns in the media aimed at persuading consumers to purchase national products, and the need for referential groups and consumer protection association to motivate consumers to purchase national products.